Uberização do trabalho: precarização ou oportunidade? análise do fenômeno sob a perspectiva de motoristas de aplicativo da cidade de Curitiba e região metropolitana durante a pandemia da COVID-19 - Ferreira, Fernanda Santana da Silva (2021)
The present study began with a systematic literature review on the topic “Uberization”, which allowed us to identify two main approaches under which the theme has been investigated in the academic context: emerging business model and transforming agent of labor relations. Focusing on the latter, this research sought to broaden the understanding of the Uberization phenomenon by analyzing the working conditions faced by app workers during the COVID19 pandemic, to verify whether the work they performed could be considered a source of precariousness or an opportunity. To achieve the proposed objective, semistructured interviews were conducted with 21 drivers of the Uber digital platform in the city of Curitiba and its Metropolitan Region, which were transcribed and analyzed using the Content Analysis technique as proposed by Bardin (2016). We concluded that work mediated by digital platforms brings more precariousness than opportunities to the workers, given the conditions of social helplessness, instability in terms of remuneration and working hours, in addition to the lack of autonomy and sole responsibility for costs and risks involved in the activity. We believe that we were able to contribute to the expansion of knowledge about “Uberization” and the consolidation of this theme as an object of investigation, important for the debate on recent changes in the world of work.